Automated dual‐axis planar solar tracker with controllable vertical displacement for concentrating solar microcell arrays. (15th November 2016) - Lim, Taehoon; Kwak, Pyo; Song, Kwangsun; Kim, Namyun; Lee, Jongho
Abstract: Concentrator photovoltaics are able to maintain power output for extended hours while reducing the quantity of expensive high performance compound semiconductor solar materials. One of the limitations in concentrator photovoltaics is the bulky and heavy form factors of solar tracking systems which usually require dedicated installation locations and resistance to wind loading. This paper describes a planar solar tracker that requires only micro or millimeter scale lateral and vertical displacements of a microlens array to maintain both the optimum lateral locations and focal lengths at various incident angles of light, using dual‐axis actuations. Experimental results for lateral solar tracker were obtained under a solar simulator considering the effects of the rotation and revolution of the Earth, and under the Sun on a rooftop with the actual system, to demonstrate the concept and practical performance. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This work presents a planar solar tracker that requires only micro or millimeter scale lateral and vertical displacements of a microlens array to maintain both the optimum lateral locations and focal lengths at various incident angles of light, using dual‐axis actuations only. Experimental results for the lateral solar tracker obtained under a solar simulator, and under the Sun on a rooftop with the actual system, demonstrate the concept and practical performance. Concentrator photovoltaics are able to maintain power output for extended hours with lower costs. One of the limitations in concentrator photovoltaics is the bulky and heavy form factors of solar tracking systems. This paper describes a planar solar tracker that requires only micro or millimeter scale lateral and vertical displacements of a microlens array using dual‐axis actuations. Experimental results were obtained under a solar simulator considering the effects of the rotation and revolution of the Earth, and under the Sun on a rooftop to demonstrate the concept and practical performance.